Deep Learning Analysis Using 18F-FDG PET/CT to Predict Occult Lymph Node Metastasis in Patients With Clinical N0 Lung Adenocarcinoma - Ouyang, Ming-li; Zheng, Rui-xuan; Wang, Yi-ran; Zuo, Zi-yi; Gu, Liu-dan; Tian, Yu-qian; Wei, Yu-guo; Huang, Xiao-ying; Tang, Kun; Wang, Liang-xing (Frontiers in Oncology, 2022)
Introduction: The aim of this work was to determine the feasibility of using a deep learning approach to predict occult lymph node metastasis (OLM) based on preoperative FDG-PET/CT images in patients with clinical N0 (cN0) lung adenocarcinoma. Materials and Methods: Dataset 1(for training and internal validation) included 376 consecutive patients with cN0 lung adenocarcinoma from our Hospital between May 2012 and May 2021. Dataset 2 (for prospective test) used 58 consecutive patients with cN0 lung adenocarcinoma from June 2021 to February 2022 at the same center. Three deep learning models including PET alone, CT alone and combined model were developed for the prediction of OLM. The performance of the models was evaluated on internal validation and prospective test in terms of accuracy, sensitivity, specificity and areas under the receiver operating characteristic curve (AUCs). Results: The combined model incorporating PET and CT showed the best performance, achieved an AUC of 0.81 (95% confidence interval [CI]: 0.61, 1.00) in the prediction of OLM in internal validation set (n = 60) and an AUC of 0.87 (95% CI: 0.75, 0.99) in prospective test set (n = 58). The model achieved 87.50% sensitivity, 80.00% specificity and 81.00% accuracy in the internal validation set, and achieved 75.00% sensitivity, 88.46% specificity and 86.60% accuracy in the prospective test set. Conclusion: This study presented a deep learning approach to enable the prediction of occult nodal involvement based on the PET/CT images before surgery in cN0 lung adenocarcinoma, which would help clinicians select patients who would be suitable for sublobar resection.